Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan SAK EMKM Dengan Aplikasi SIAPIK - Rahmat, Wahyu Rifki; Sulastri, Sulastri; Fathiah, Fathiah (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2022)
Recording of financial statements is one of the important things in the continuity of a company, both large companies and micro, small and medium enterprises (MSMEs). Every company must have financial reports that are good and correct according to accounting standards, this aims to determine the condition and financial performance of the company and can help owners. This study aims to assist MSMEs in preparing financial reports based on SAK EMKM. Research conducted at PT. Tikar Ruyung by conducting interviews and asking for financial report data to be processed so that it is in accordance with SAK EMKM. The preparation of financial reports uses a qualitative method with the SIAPIK application starting from to January to June 2022. The results of the research show that PT. Tikar Ruyung in compiling financial reports is still very simple and not in accordance with accounting standards. Recording of financial statements of PT. Tikar Ruyung is done based on cash receipts and disbursements. Factors that cause financial records at PT. Tikar Ruyung is still very simple is due to a lack of human resources and understanding of financial reports. The study produced financial reports in accordance with SAK EMKM using the SIAPIK application consisting of income statements, statements of financial position and notes on financial statements in January to June 2022.